2020
DOI: 10.1021/acsnano.0c03496
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and Photoconductivity of a p-Type Organic Semiconductor under Ultrastrong Coupling

Abstract: It has been shown that light-matter strong coupling of materials can lead to modified and often improved properties which has stimulated considerable interest. While charge transport can be enhanced in n-type organic semiconductors by coupling the electronic transition and thereby splitting the conduction band into polaritonic states, it is not clear whether the same process can also influence carrier transport in the valence band of p-type semiconductors. Here we demonstrate for the first time that it is inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 48 publications
1
71
0
Order By: Relevance
“…It has been seen in the past years that the mere presence of such polaritonic states in the coupled system lead to new material properties. For instance, strongly coupled organic molecules could enhance the conductivity 15,16 , the rate of energy transfer 17 of molecules, and furthermore, modify the work function 18 and chemical reactions of molecules 19,20 . Besides, recent studies also showed that second-harmonic generation and third harmonic generation could be enhanced in the presence of polaritonic states [21][22][23][24] .…”
mentioning
confidence: 99%
“…It has been seen in the past years that the mere presence of such polaritonic states in the coupled system lead to new material properties. For instance, strongly coupled organic molecules could enhance the conductivity 15,16 , the rate of energy transfer 17 of molecules, and furthermore, modify the work function 18 and chemical reactions of molecules 19,20 . Besides, recent studies also showed that second-harmonic generation and third harmonic generation could be enhanced in the presence of polaritonic states [21][22][23][24] .…”
mentioning
confidence: 99%
“…However, in that respect we note that previous studies reporting enhanced conductivity upon strong coupling also utilized organic semiconductors known to form polycrystalline films, and with similar charge carrier mobilities. 27,28 We further note that the exciton-polaritons in our system carry no net charge, because they originate from excitons consisting of one negatively charged electron and one positively charged hole. Future work may investigate charge transport also for polaritons composed of quasiparticles with nonzero net charge, such as polaron-polaritons 41,42 or trion-polaritons, 38,43 which can readily drift under applied external electric fields.…”
Section: Resultsmentioning
confidence: 83%
“…23 This cavity-enhanced exciton transport was supported by theoretical studies. 24,25 Theoretical reports also proposed that the formation of hybrid polariton states can affect charge transport, either by opening an additional transport channel contributing to electrical current, 26 or by delocalizing not only the polaritonic states but also the electronic states in the conduction 27 and valence bands, 28 thereby overcoming limitations due to molecular disorder. Excitingly, such coupling-induced enhancements of charge transport were experimentally reported in both n-type 27 and p-type 28 organic semiconductors strongly coupled to plasmonic nanohole arrays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 There are mainly three mechanisms proposed for this observed phenomenon, that include: (i) effective mass of the polaritonic state, (ii) molecular coherence and (iii) work function modification under strong coupling. 21,23,24,25,26 Both experimental and theoretical studies suggest that either one or all of the above mechanisms may operate together to boost the transport in the medium. 21 Organic electronics is based on hopping mechanism and hence molecular packing has a huge role in controlling their electrical properties.…”
mentioning
confidence: 99%